Green Nanoemulsion Stabilized by In Situ Self-Assembled Natural Oil/Native Cyclodextrin Complexes: An Eco-Friendly Approach for Enhancing Anticancer Activity of Costunolide against Lung Cancer Cells - Nabil A. Alhakamy; Shaimaa M. Badr-Eldin; Osama A. A. Ahmed; Hibah M. Aldawsari; Solomon Z. Okbazghi; Mohamed A. Alfaleh; Wesam H. Abdulaal; Thikryat Neamatallah; Omar D. Al-hejaili; Usama A. Fahmy (MDPI AG, 2022)
Lung cancer is the second-most deadly malignancy worldwide, of which smoking is considered a major risk factor and causes 75-80% of lung cancer-related deaths. Costunolide (CTD) extracted from plant species Saussurea, Aucklandia, and Inula exhibits potent anticancer properties, specifically in lung cancer and leukemia. Several nanoemulsions were prepared and optimized using a three-factor Box-Behnken experimental design. The optimized green nanoemulsion (GNE) showed a vesicle size of 199.56 nm. The IC50 values revealed that A549 cells were significantly more sensitive to the optimized CTD formula than the plain formula and raw CTD. A cell cycle analysis revealed that the optimized CTD formula treatment resulted in significant cell cycle arrest at the S phase. The results also indicated that treatment with the CTD formula significantly increased caspase-3, Bax, Bcl-2, and p53 mRNA expression compared to the plain formula and CTD raw. In terms of the inflammatory markers, the optimized formula significantly reduced the activity of TNF-α and NF-κB in comparison with the plain formula and raw drug only. Overall, the findings from the study proved that a CTD GNE formulation could be a promising therapeutic approach for the treatment of lung cancer.